2022
DOI: 10.1186/s12906-022-03628-8
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of herbal medicine use and contributing factors among pregnant women on antenatal care follow-up at Dessie Referral Hospital, Northeast Ethiopia

Abstract: Background Herbal medicines are widely used in the world especially in developing countries. Pregnant women use herbal products to treat pregnancy related illnesses due to prior experience of herbal medicine use and easy accessibility of the products with less cost. However, herbal products could affect fetal growth and contribute to maternal and fetal morbidity and mortality. Herbal drug use during pregnancy is not well studied in Ethiopia specifically in northeast Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6). Regarding the geographical distribution of included studies, a majority of them were conducted in Africa 66 69 77 81 82 89 91 95 98 100 101 105 106 115 116 119 121–123 129 132–135 137–140 143 144 146 150 153 156 158–164. Lastly, 21 out of 111 studies presented findings related to pregnant women’s disclosure of HM use to their healthcare providers 27 70 73 83 85 86 91 109 110 115 117 122 125 126 129 133 142 149 155 160 164…”
Section: Resultsmentioning
confidence: 99%
“… 2022 ), 51.2%-65.6% in Ethiopia (Belayneh et al. 2022 ; Wake and Fitie 2022 ), 71.80% in Bangladesh (Jahan et al. 2022 ), and 67.45% in Morocco (Kamel et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 ), and Ethiopia (Belayneh et al. 2022 ). In addition, it was observed that some of those women perceived that they had better knowledge about herbal medicine than the physicians/nurses and would persist in using it against medical advice.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a two-way referral system and linkage between ATMs and conventional health systems in most African nations creates mistrust between the two systems to the detriment of patients. As a result, most patients may not disclose ATMs use, thus increasing the potential for adverse reactions and the possibility of delayed diagnosis, among other risks 39 40. The unregulated status of many THPs and their medicines also creates accountability gaps increasing the potential for sub-standard and counterfeit products, professional malpractice and unethical conduct.…”
Section: Benefits and Challenges Associated With The Use Of Atmsmentioning
confidence: 99%